2009
DOI: 10.1016/j.nuclphysa.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Exchange terms in the two-nucleon induced non-mesonic weak decay of Λ-hypernuclei

Abstract: The contribution of Pauli exchange terms to the two-nucleon induced non-mesonic weak decay of 12 Λ C hypernuclei, ΛN N → nN N (N = n or p), is studied within a nuclear matter formalism implemented in a local density approximation. We have adopted a weak transition potential including the exchange of the complete octets of pseudoscalar and vector mesons as well as a residual strong interaction modeled on the Bonn potential. The introduction of exchange terms turns out to reduce the two-nucleon induced non-meson… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 46 publications
6
48
0
Order By: Relevance
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the nuclear recoil is also taken into account as a new feature of our approach, which is applied to 12 Λ C. Formally, this corresponds to implement translational invariance and exact momentum conservation in the nonmesonic decays. The same microscopic approach showed that ground state correlation contributions are crucial for a detailed calculation of the rates, the asymmetry parameter and the nucleon emission spectra [19,20,22,24]. Less pronounced effects were reported by including the ∆-baryon resonance [23].…”
mentioning
confidence: 94%
“…Different measurements of single and coincidence spectra of the nucleons emitted in hypernuclear nonmesonic decay, by the SKS Collaboration at KEK [5,6] and the FINUDA Collaboration at LNF [7][8][9], their theoretical analysis and the many calculations incorporating: 1) complete meson-exchange weak interaction potentials (with both oneand two-meson exchange) [10][11][12][13], 2) the description of the ΛN and NN short-range correlations in terms of quark degrees of freedom [14], 3) twonucleon induced modes, ΛNN → nNN [15][16][17][18][19][20], as well as 4) nucleon final state interactions [21][22][23], have proven crucial to solve the "Γ n /Γ p puzzle", in a continuous dialogue and exchange between theory and experiment. The two-nucleon induced decay mechanism is rather well understood at present too, although the data on Γ 2 are still affected by large error bars.…”
mentioning
confidence: 99%
See 2 more Smart Citations